LIN28B enhanced tumorigenesis in an autochthonous KRASG12V-driven lung carcinoma mouse model - Meder, Lydia; Koenig, Katharina; Dietlein, Felix; Macheleidt, Iris; Florin, Alexandra; Ercanoglu, Meryem S.; Rommerscheidt-Fuss, Ursula; Koker, Mirjam; Schoen, Gisela; Odenthal, Margarete; Klein, Florian; Buettner, Reinhard; et al. (Oncogene, 2018)
LIN28B is a RNA-binding protein regulating predominantly let-7 microRNAs with essential functions in inflammation, wound healing, embryonic stem cells, and cancer. LIN28B expression is associated with tumor initiation, progression, resistance, and poor outcome in several solid cancers, including lung cancer. However, the functional role of LIN28B, especially in non-small cell lung adenocarcinomas, remains elusive. Here, we investigated the effects of LIN28B expression on lung tumorigenesis using LIN28B transgenic overexpression in an autochthonous KRAS G12V -driven mouse model. We found that LIN28B overexpression significantly increased the number of CD44+/CD326+ tumor cells, upregulated VEGF-A and miR-21 and promoted tumor angiogenesis and epithelial-to-mesenchymal transition (EMT) accompanied by enhanced AKT phosphorylation and nuclear translocation of c-MYC. Moreover, LIN28B accelerated tumor initiation and enhanced proliferation which led to a shortened overall survival. In addition, we analyzed lung adenocarcinomas of the Cancer Genome Atlas (TCGA) and found LIN28B expression in 24% of KRAS-mutated cases, which underscore the relevance of our model.
CRIS-Team Scopus Importer:2023-03-21